Wind noise source filtering and transmission study through a side glass of DrivAer model. (March 2020) - He, Yinzhi; Schröder, Simon; Shi, Zihao; Blumrich, Reinhard; Yang, Zhigang; Wiedemann, Jochen
Abstract: In order to study flow induced convective and acoustic pressure fluctuations around a car side window and their transmission characteristics and mechanism to the interior, a full-size DrivAer clay model equipped with a normal front left side glass was employed. In this way, the side glass is the exclusive transmission path for the exterior pressure to the isolated acoustic cabin behind the glass. By means of a compressible CFD simulation based on the Spalart-Allmaras DES model combined with an improved wavenumber decomposition algorithm particularly implemented in MATLAB, the two kinds of pressure fluctuations on the side glass of DrivAer model were separated successfully. Subsequently, their contributions to interior noise were calculated with SEA method individually. Since the predicted total interior noise level at the middle and high frequency range shows good agreement with the tested result, the reliability of the implemented wavenumber filtering approach was indirectly validated. The contributions of these two fractions indicate that the acoustic pressure fluctuations take much higher transmission efficiency than the convective one, especially for frequencies above the coincidence frequency of the glass, the contribution of the acoustic fraction is even absolutely dominant.